GM2-gangliosidosis, type I (Tay – Sachs disease) in the pediatrician practice - Natalia V. Zhurkova; Nato D. Vashakmadze; Natella V. Sukhanova; Olga B. Gordeeva; Natalia S. Sergienko; Ekaterina Yu. Zaharova (Педиатрическая фармакология, 2021)
Background. GM2-gangliosidosis, type I (Tay-Sachs disease) is rare hereditary disease caused by mutations in the HEXA gene encoding the alpha subunit of lysosomal hexosaminidase A. It leads to accumulation of GM2-ganglioside in lysosomes and cell death. The major clinical signs of this disease are regression of motor and psychoverbal skills, progressive macrocephaly, diffuse muscle hypotension, convulsive disorder. Almost all patients with this disease have the “cherry red spot” symptom on the fundus of the eye.Clinical case description. We show clinical description of the patient with disease manifested with the lesion of visual analyzer. The child was sent for geneticist’s consultation due to revealed ophthalmic picture of the “cherry red spot” symptom on the fundus of the eye. Molecular genetic testing has revealed in the patient c.1274_1278 dupTATC (CI 880091) mutation in homozygous state in HEXA gene.Concllusion. Differential diagnosis of this disease should be performed with other diseases from the group of inherited metabolic diseases associated with early regression of psychomotor skills, progressive vision loss, “cherry red spot” symptom on the fundus of the eye and convulsive disorder